Development of the Passive and Active Meat-Animal Dissociation Scale (MADS) - Nora C. G. Benningstad; Hank Rothgerber; Jonas R. Kunst (Psychology of Human-Animal Intergroup Relations)
Many individuals like eating meat but condemn causing harm to animals. Dissociating meat from its animal origins is one way to avoid the cognitive dissonance this ‘meat paradox’ elicits. While the significance of meat-animal dissociation for meat consumption is well-established, a recent literature review suggested that it consists of two distinct tendencies. First, people may differ in the degree to which they passively disassociate meat from its animal origins. Second, they may differ in the extent to which they actively dissociate to decrease dissonance. By developing and validating a scale in three pre-registered studies using samples of American and British meat-eaters, the present investigation aimed to quantitatively establish whether these two proposed tendencies constitute distinct constructs with different relations to dietary preferences, meat-related cognition, and affect. Study 1 (n = 300) provided initial support for a normally-distributed scale with two orthogonal dimensions that were systematically and differently related to a range of individual differences and dietary preferences. In Study 2 (n = 628), both dimensions were non-responsive to short-term cues that highlight the animal-meat link but predicted dietary preferences independent of them. Finally, Study 3 (n = 231) showed that the dissociation dimensions predict dietary preferences even in people working in the meat industry who have long-term exposure to cues that connect meat with its animal origins. Together, the results of the three studies supported the notion that people’s dissociation tendencies can be divided into two qualitatively distinct tendencies. Implications and avenues for future research are discussed.